Comparison between six different carboxymethylcelluloses used as enological products for the tartaric stabilization of red wines - Pittari, Elisabetta (2017)
Mestrado Vinifera Euromaster - Instituto Superior de Agronomia - UL / Institut National D'Etudes Superieures Agronomiques de Montpellier